Blue Light Hazard Optimization for White Light‐Emitting Diode of Mn2+‐Activated 0D Cs3Cu2Br5 Perovskite Materials - Yaoyu Liu; Xixi Zheng; Zongshuai Ji; Tianyu Wang; Haixia Yu; Bing Teng; Shaohua Ji (Advanced Materials Interfaces, 2023)
Abstract The zero‐dimensional perovskite‐like derivative Cs3Cu2X5 (X = Cl, Br, I) with self‐trapped excitons (STEs) photoluminescence (PL) has attracted tremendous interest in the field of optoelectronics. Nonetheless, it is challenging for Cs3Cu2Br5 material to attain full visible spectrum emission and prevent light‐induced photochemical damage to the retina (blue light hazard) in applications. Herein, Mn2+ is chosen as the dopant to alloy into Cs3Cu2X5 via a one‐step solid state synthesis method. Significantly, the series of Mn2+‐doped show the emission peak of 460 nm STEs and the emission peak of 550 nm Mn2+. More importantly, the high energy absorption of Mn2+ facilitates the transfer of exciton energy, contributing to a reduction in blue emission peak at 460 nm. Simultaneously, ≈17.5% of Mn2+ is alloyed into the Cs3Cu2X5lattice to induce the energy transfer channels from the Cs3Cu2X5 host to the Mn2+ guest to lead to the emission of Mn2+, which broadens emission spectrum (400–620 nm) and realizes 80% reduction of the blue emission peak at 460 nm. Additionally, a white light‐emitting diodes can decrease the blue emission band via 71.45% and an ultrahigh color rendering index (CRI) of 94.5 is produced using the 17.5% Mn2+: Cs3Cu2X5 perovskite‐like derivative powder material.